STUDENTS OF ENGLISH IN ALGERIAN UNIVERSITY AND THEIR PERSPECTIVES OF EMPLOYABILITY AFTER GRADUATION - Belaid, Louiza; Sarnou, Hanane (LLT Journal: A Journal on Language and Language Teaching, 2019)
Success at university requires achieving a high degree; however, after university, it is perceived through the achievement of financial satisfaction. This investigative work examines the students perspectives of their professional careers after graduation from university. Our objective is to see the extent to which students are prepared to insert in the professional life. A questionnaire is used as an instrument in this enquiry to fifty five students at the University of Ibn Khaldoun- Tiaret. The results reveal that students are not fully qualified to take part in the state service and they fear unemployment due to the lack of job opportunities, the latter is believed to be caused by the large number of university graduates. For this, reviewing the admission of students at university is compulsory, that is to say, reducing the number of bachelors by accepting only competent learners and then providing a job opportunity for each graduate respectively on the basis of their potential.